Activated Human Memory B Lymphocytes Use CR4 (CD11c/CD18) for Adhesion, Migration, and Proliferation - Nagy-Baló, Zsuzsa; Kiss, Richárd; Menge, Alina; Bödör, Csaba; Bajtay, Zsuzsa; Erdei, Anna (Frontiers in Immunology, 2020)
Complement receptors CR3 (CD11b/CD18) and CR4 (CD11c/CD18) of myeloid cells are known for long to participate in actin linked functions like phagocytosis, adhesion, and migration. The expression and role of these two β2-integrins however, in human B lymphocytes have only scarcely been studied so far, although it has been shown recently that CD11c+ B cells are mainly memory cells. In our systematic study we investigated B cells isolated from tonsils and peripheral blood of healthy donors. We found, that while only 5% of resting tonsillar B cells expressed CD11c, their number increased up to 26% after 3 days of BCR stimulation. Lower, but still remarkable percentage of B lymphocytes were positive for CD11c after stimulation via TLR9 alone or via TLR9 and BCR simultaneously. At the same time, we detected no significant expression of CD11b on resting or activated tonsillar B cells. Blood B lymphocytes showed a similar expression pattern of both β2-integrins. We demonstrated that CD11c molecules appearing on the surface of B cells are newly synthesized, reaching the number of 9500 per activated B cell. We found that CR4 expressing B cells belong to the memory pool and the increase of CD11c expression on tonsillar B cells upon BCR mediated activation occurs parallel with class switching. Analysis of the function of CD11c revealed, that this β2-integrin contributes to the adhesion and migration of activated B lymphocytes. We also demonstrated that the CR4 mediated adhesion promotes the proliferation of the BCR activated cells. Our studies are the first to demonstrate that CD11c expressed on BCR-activated human B cells are not only passive markers but functional drivers of memory B cell responses.